Alirocumab after acute coronary syndrome in patients with a history of heart failure. (18th December 2021) - White, Harvey D; Schwartz, Gregory G; Szarek, Michael; Bhatt, Deepak L; Bittner, Vera A; Chiang, Chern-En; Diaz, Rafael; Goodman, Shaun G; Jukema, Johan Wouter; Loy, Megan; Pagidipati, Neha; Pordy, Robert; et al.
Abstract: Aims: Patients with heart failure (HF) have not been shown to benefit from statins. In a post hoc analysis, we evaluated outcomes in ODYSSEY OUTCOMES in patients with vs. without a history of HF randomized to the proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitor alirocumab or placebo. Methods and results: Among 18 924 patients with recent acute coronary syndrome (ACS) receiving intensive or maximum-tolerated statin treatment, the primary outcome of major adverse cardiovascular events (MACE) was compared in patients with or without a history of HF. The pre-specified secondary outcome of hospitalization for HF was also analysed. Overall, 2815 (14.9%) patients had a history of HF. Alirocumab reduced low-density lipoprotein cholesterol and lipoprotein(a) similarly in patients with or without HF. Overall, alirocumab reduced MACE compared with placebo [hazard ratio (HR): 0.85; 95% confidence interval (CI): 0.78–0.93; P = 0.0001]. This effect was observed among patients without a history of HF (HR: 0.78; 95% CI: 0.70–0.86; P < 0.0001), but not in those with a history of HF (HR: 1.17; 95% CI: 0.97–1.40; P = 0.10) ( P interaction = 0.0001). Alirocumab did not reduce hospitalization for HF, overall or in patients with or without prior HF. Conclusion: Alirocumab reduced MACE in patients without a history of HF but not in patients with a history of HF. Alirocumab did not reduce hospitalizations for HF in either group. Patients with a history of HF are a high-risk group that does not appear to benefit from PCSK9 inhibition after ACS. Structured Graphical Abstract: